Addition of shredded stem of sugar cane varieties to artificial diets on the biology of Diatraea saccharalis (F.) (Lepidoptera: Crambidae) - Boiça Jr., Arlindo Leal [UNESP]; Leonelo, Aluízio Fumagalli [UNESP]; De Jesus, Flávio Gonçalves (Universidade Estadual de Londrina, 2011)
It was studied the incorporation or not of shredded stems of sugarcane varieties to artificial diets and their effect in the biology of Diatraea saccharalis (Fabr., 1794) (Lepidoptera: Crambidae) under laboratory conditions. The experiment was carried out at the Department of Plant Protection of FCAV- UNESP, Jaboticabal, São Paulo, Brazil, in 2007, using diets with different amounts of their components (100, 75, 25 e 25% of concentration of the standard diet). The experiment had a complete randomized design in a 4x3 factorial scheme, using 4 concentrations of diets and three treatments, in a total of 12, with 6 replications. The larval, pupal an total periods and viability were evaluated, as well as the larval weight at 15 days, the pupal weight after 24 hours and the longevity of adults without feeding. The dietwith 25% concentration of the components compared to the standard diet had a negative effect in the development of D. saccharlis larvae. Shredded dry stalks incorporated or not to the diet affected only the larval and pupal weight whereas the larval weight was more affected when the resistant (RB83-5486) and susceptible (SP80-3280) varieties due to the use of diet with 50% of its components. The diet with 100% concentration of its components are more favorable to the development of D. saccharalis, with 25% while that is less favorable. The diet with 100% concentration of the components associated with the presence of SP80-3280 (susceptible) stem variety provides greater larval weight. The weights of larvae and pupae of insects are negatively affected when RB83-5486 (resistant) shredded dry stem variety is incorporated into the diet. regarding to larval weight the diet with 50% of the concentration of its components provides better discrimination between genotypes resistant and susceptible to sugarcane borer.
Dietas artificiais incorporadas ou não a colmos triturados de variedades de cana-de-açúcar na biologia de Diatraea saccharalis (F.) (Lepidoptera: Crambidae)
Keywords: Host plant resistance; Insecta; Sugarcane borer